Spatial Relationships of the Impact of Using Modern Irrigation Methods on the Production of Wheat Crop in the Holy Karbala Governorate (Journal of the College of Basic Education, 2026)
This study is based on knowledge of the spatial analysis of the effect of using modern irrigation methods on the production of wheat crops in the Holy Karbala Governorate and the interpretation of this according to a number of variables represented by (cultivated area, production costs and product skill). In the production of the wheat crop in the holy Karbala governorate, it is the size of agricultural holdings and production costs, and that the increase in cultivated areas in the governorate was a result of the expansion of the use of modern irrigation methods through which production quantities increased significantly than they were in previous years.